CANDI SELOGRIYO SEBAGAI SUMBER BELAJAR SEJARAH AGAMA HINDU BAGI PESERTA DIDIK JENJANG SEKOLAH MENENGAH ATAS - Arrazaq, Naufal Raffi; Tasnur, Irvan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Research related to the use of Candi Selogriyo as a source of learning Hindu history for high school students has not been studied in depth by previous researchers. The purpose of this study is to analyze the potential of Candi Selogriyo as a source of learning Hindu history for high school students. This research uses qualitative methods. Research data uses literature studies in the form of books, journals, and internet pages. The results showed that Candi Selogriyo has the potential to be used as a source of learning Hindu history. The basis for this use is the relationship between Candi Selogriyo and the curriculum of Indonesian History class X SMA / MA KD 3.5 related to learning materials about the entry process of Hindu religion and culture in Indonesia. The development of Candi Selogriyo material as a source of learning the history of Hinduism during the Mataram Kuno Kingdom is the iconography of Hindu-style statues during the Mataram Kuno Kingdom, the technology of building Hindu-style temples, and the preservation of historical relics of Hindu-style temples. The model of using Candi Selogriyo as a source of learning Hindu history for high school students can be done with systematic steps, namely (1) identifying KD subjects in Indonesian History, (2) formulating learning objectives and indicators, (3) reviewing the content of material at Candi Selogriyo, (4) designing learning models and media, and (5) evaluating learning.